The Students’ Strategies in Developing Their Ideas in Writing Essay - Dhani Oktavianti; Paidi Gusmuliana; Eka Apriani (Yayasan Karinosseff Muda Indonesia, 2021)
This research aimed to find out the students strategies in developing their ideas in writing essay in at fourth semester in IAIN Curup who have best score in writing essay. This research is a descriptive research which is presented in qualitative way. The researcher have two research questions, the research question are: the first what are the students’ strategies in developing their ideas in writing essay. The second what are the students’ problem in developing their ideas in writing essay. Subject of the research was 10 students at fourth semester on 2019-2020 academic years of English Study Program at IAIN Curup. The instrument of the research was used interview. In analysis data, first researcher identified and check data that be collected. After that, researcher describes all the data. Next the researcher classified the data of the students which is used the strategy or not.